2017
DOI: 10.1016/j.foodhyd.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of water-in-oil-in-water emulsions by low frequency ultrasound using skim milk and sunflower oil

Abstract: 15Double emulsions of water-in-oil-in-water (W1/O/W2) type were prepared in skim milk using 16 20 kHz ultrasound. Ultrasonic emulsification provides a simple and quick yet effective protocol 17 by which double emulsions can be created using low amounts of surfactant. The fat 18 displacement and shelf stability of the emulsions were found to be dependent on the amount of 19 sonication power delivered during the dispersion of the W1/O emulsion into skim milk. 20 Acoustic intensity was manipulated to control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 38 publications
4
48
0
2
Order By: Relevance
“…The highest encapsulation efficiency after the storage period was found for w/o/w emulsions without hydrocolloid. This finding confirmed the importance of casein-emulsifying properties [27], but droplet size uniformity (Fig. 4b) was clearly better when carrageenan GENULACTA NM-300 was added.…”
Section: Milk As the Internal Water Phasesupporting
confidence: 77%
“…The highest encapsulation efficiency after the storage period was found for w/o/w emulsions without hydrocolloid. This finding confirmed the importance of casein-emulsifying properties [27], but droplet size uniformity (Fig. 4b) was clearly better when carrageenan GENULACTA NM-300 was added.…”
Section: Milk As the Internal Water Phasesupporting
confidence: 77%
“…Whereas sonication at a high amplitude normally results in loss of inner water droplets and their encapsulated ingredients, Tang and Sivakumar () have reported that a W/O/W emulsion can be successfully prepared by “modified” sonication—that is, under conditions of minimal cavitation at low amplitude. In preparing submicron W/O/W emulsions containing ferrous fumarate and ascorbic acid in the W1 phase, Tang and Sivakumar () used an Ultra‐Turrax to make the W/O and W/O/W premixes, and then they homogenized the premixes further using a specially designed “liquid whistle hydrodynamic cavitation reactor.” Leong and others () also recently used low‐energy sonication to disperse a primary W1/O emulsion containing skim milk as W1 phase, thereby enriching the milk with sunflower oil (35% encapsulation yield).…”
Section: Preparation Of Double Emulsionsmentioning
confidence: 99%
“…The continuous liquid phase of the food may replace the W2 phase of the original DE system, or alternatively the W2 phase of the enriched food product may be prepared directly. In the manufacture of a stable milk product (W2 phase) produced by dispersing a W1/O emulsion into skim milk, Leong and others () arranged the osmotic pressure in the W1 phase to be about 10 times higher than that in the W2 phase. In this formulation, the primary W1/O emulsion, containing a W1 phase of skim milk + 8 wt% NaCl, was emulsified into sunflower oil with 10 wt% Span 80.…”
Section: Preparation Of Double Emulsionsmentioning
confidence: 99%
“…To measure droplets, the refractive index of both emulsifiers (Span 80 = 1.48, PGPR = 1.464) and viscosity of sesame oil (viscosity =62 cp) at 25°C were introduced to the apparatus software. All measurements were done three times after overnight storage of samples at ambient temperature (Leong, Zhou, Kukan, Ashokkumar, & Martin, ).…”
Section: Methodsmentioning
confidence: 99%